2013
DOI: 10.1128/iai.00219-13
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi Linear Plasmid 28-3 Confers a Selective Advantage in an Experimental Mouse-Tick Infection Model

Abstract: Borrelia burgdorferi, the bacterium that causes Lyme disease, has a unique segmented genome consisting of numerous linear and circular plasmids and a linear chromosome. Many of these genetic elements have been found to encode factors critical for B. burgdorferi to complete the infectious cycle. However, several plasmids remain poorly characterized, and their roles during infection with B. burgdorferi have not been elucidated. To more fully characterize the role of one of the four 28-kb linear plasmids, lp28-3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…B. burgdorferi organisms that are unable to produce BBA03, a surface protein of unknown function, are capable of infecting mice yet were outcompeted in dual-infection studies with wild-type bacteria (30). Similar analyses indicated that the naturally occurring replicon lp28-3 encodes at least one factor that makes a significant contribution to mammalian infection (31). Mutant B. burgdorferi organisms that are unable to produce the surface-exposed fibronectin-binding protein BBK32 are capable of infecting mice (32).…”
Section: Discussionsupporting
confidence: 51%
“…B. burgdorferi organisms that are unable to produce BBA03, a surface protein of unknown function, are capable of infecting mice yet were outcompeted in dual-infection studies with wild-type bacteria (30). Similar analyses indicated that the naturally occurring replicon lp28-3 encodes at least one factor that makes a significant contribution to mammalian infection (31). Mutant B. burgdorferi organisms that are unable to produce the surface-exposed fibronectin-binding protein BBK32 are capable of infecting mice (32).…”
Section: Discussionsupporting
confidence: 51%
“…CspZ was shown not essential for spirochetes acquisition from mammalian hosts to ticks (Coleman et al, 2008). However, fewer mice develop antibody reactivity against whole spirochete cell lysates after being fed on by the ticks carrying a B. burgdorferi strain missing lp28-3 plasmid which encodes cspZ, compared to wild-type parental spirochete strain (Dulebohn et al, 2013). These findings suggest that the proteins encoded by lp28-3 (e.g., CspZ) facilitate spirochete to establish an infection and disseminate to distal sites after tick bites.…”
Section: The Role Of Cspz In Promoting Spirochete Dissemination Aftermentioning
confidence: 99%
“…R. Casjens et al, 2018;Mongodin et al, 2013). Borrelia plasmids contain genes related to host and vector adaptation and absence of certain plasmid types have been linked to reduced infectivity (S. R. Casjens et al, 2018;Dulebohn, Bestor, & Rosa, 2013;Ellis et al, 2013;Embers, Alvarez, Ooms, & Philipp, 2008;Grimm et al, 2004Grimm et al, , 2005Lin, Diuk-Wasser, Stevenson, & Kraiczy, 2020). Therefore, their presence could influence the evolution of these bacteria and should be considered.…”
Section: Resultsmentioning
confidence: 99%